Ugotavljanje deklariranih bakterij v probiotičnih prehranskih dopolnilih in zdravilih na slovenskem trgu - Bogovič Matijašić, Bojana (Farmacevtski vestnik, 2010)
There are an increasing number of probiotic food supplements or medicinal products on the Slovenian market. Probiotic microorganisms in these products have to be viable otherwise the effects may not be expected. Producers, distributors or sellers do not decide often for the analysis of probiotic products in independent laboratories since Slovenian legislation does not require control of their content before being sold. The aim of this study was to survey the suitability of probiotic food supplements and medicinal products (OTC) available in Slovenian pharmacies. Five food supplements out of 20 tested contained enough viable microorganisms while the number was not declared in two products. In six products the viable representatives of all declared species were not found by PCR method. Both probiotic medicinal products were suitable regarding the species composition and number of probiotic bacteria. Results indicate the need for better quality control of such products.
Keywords: bacteria; bakterije; drug; kvaliteta; mikrobiologija hrane; prehranska dopolnila; probiotiki; zdravila